ChemInform Abstract: Synthesis and Antibacterial Activity of New Diaryldiamines. Issue 19 (18th April 2013) - Samrin, Farhana; Sharma, Akash; Khan, Inshad Ali; Puri, Sadhna
Abstract Several new quinolones and quinazolines (V), (XIII), (XVIII) are synthesized from cheap and readily available starting materials.